Analysis of Competency and Work Discipline Towards Performance of the Jamrud Biru Foundation Rehabilitation Home in Bekasi - Achnihadian, Janjan; Ludfi Arifin, Antoni (Dinasti Publisher, 2025)
The issue of mental disorders in Indonesia continues to rise, with more than 19 million people experiencing emotional mental disorders. Yayasan Jamrud Biru in Bekasi plays a significant role in providing rehabilitation services for People with Mental Disorders (ODGJ); however, the foundation's performance is influenced by internal and external factors. This study aims to analyze the influence of competence and work discipline on the performance of the foundation's employees in delivering optimal services. Using a qualitative approach and case study design, data were collected through in-depth interviews, participatory observation, and document studies, then analyzed using NVivo software. The results show that competence and work discipline have a significant relationship with performance. The foundation's performance is supported by a reciprocal relationship between competence and the rehabilitation process, resource support, ongoing evaluation, and collaboration with other institutions. However, financial resource limitations and lack of family support pose challenges that must be addressed to improve the quality of rehabilitation services.